Influence of educational actions on transitioning of food safety culture in a food service context: Part 1 – Triangulation and data interpretation of food safety culture elements. (January 2021) - Zanin, Laís Mariano; Luning, Pieternel A.; da Cunha, Diogo Thimoteo; Stedefeldt, Elke
Abstract: Foodborne diseases still occur globally, and alongside food safety systems, food safety culture has been established as a factor in ensuring food safety. This study describes the development of a mixed-methods approach to collecting quantitative and qualitative data and interpreting the triangulated data to assess the prevailing food safety culture. The mixed-methods approach was designed based on the literature and was tested in a food service establishment at an army headquarters in Brazil. Both managers (3) and food handlers (39) participated. The quantitative (questionnaires and checklists) and qualitative (participant observations) data were triangulated using a scoring system on an interpretation grid. The scoring system typified the prevailing food safety culture (FS-culture) and its elements as reactive (score 1), reactive to active (score 1–2), active (score 2), active to proactive (score 2–3), or proactive (score 3) FS-culture. The overall prevailing FS-culture in the case study, scored 1–2. This FS-culture score was mainly attributed to the score 1 for the elements of leadership, risk perception, and management systems, styles and processes, and the score 1–2 for communication, knowledge, and work environment. The mixed-methods approach revealed an overestimation of FS-culture elements in the quantitative analysis and underestimation in the qualitative analysis. This discrepancy in results emphasises the usefulness of the concurrent analysis and highlights the need to employ triangulation to enable a comprehensive assessment of the prevailing FS-culture. The assessment provides concrete input for the development of educational actions aiming for changes in the prevailing FS-culture. Highlights: The mixed-method enabled a realistic assessment of the prevailing FS-culture. Qualitative data supported visualisation of the FS-culture in daily routine. Quantitative data indicated an overestimation of prevailing FS-culture. Discrepant quantitative and qualitative data stress the importance of triangulation. FS-culture assessment can be the basis for educational actions.